WATER QUALITY IMPROVEMENT AND ANALYSIS FOR CLOWN FISH (Amphiprion ocellaris) CULTIVATION IN A RECIRCULATION SYSTEM - Santikawati, Susi; Syafriadiman, Syafriadiman; Syawal, Henni (Asian Journal of Aquatic Sciences, 2023)
The demand for ornamental fish is currently increasing while the availability in nature is decreasing due to overfishing. Clownfish (Amphiprion ocellaris) is a type of marine ornamental fish that is widely kept in aquariums, but the problem is the rapid decline in water quality due to the activity of these fish. The recirculation system is one way that can be used in water quality management. The study aimed to analyze the type of filter used to stabilize seawater quality in clownfish (rearing containers. This research was conducted from January to April 2021 at the Research Centre of Sibolga Fisheries College. The method used was an experimental method using a one-factor Completely Randomized Design (CRD) with four treatment levels and three replications. The treatments in this study were P0 (unfiltered), P1 (cotton filter), P2 (fiber filter), and P3 (activated charcoal filter). The fish used was 2 – 3 cm in size, kept in an aquarium measuring 60x40x40cm with a stocking density of 2 fish/L of water and fed tubifex 2 times a day, at 08.00 and 18.00 WIB as much as 5% of their body weight. Parameters measured were temperature, pH, DO, salinity, ammonia, and phosphate, abundance of bacteria, phytoplankton, and survival of clownfish. Water quality measurements are carried out every 7 days. The results obtained from the improvement and analysis of water quality for the cultivation of clownfish in the recirculation system provides an influence on water quality in the rearing container. The results obtained were temperature 27.9–28.0 0C, pH 8.3–8.4, DO 7.5–8.0 mg/L, salinity 33-34 ppt, ammonia 0.04–0.06 mg/L, phosphate 0.47–0.48 mg/L and bacterial abundance 2.35x104 CFU/mL with a survival rate of 95.55%.